Family Model of Diabetes Education With a Pacific Islander Community. (December 2015) - McElfish, Pearl Anna; Bridges, Melissa D.; Hudson, Jonell S.; Purvis, Rachel S.; Bursac, Zoran; Kohler, Peter O.; Goulden, Peter A.
Purpose: The purpose of the study was to use a community-based participatory research approach to pilot-test a family model of diabetes education conducted in participants' homes with extended family members. Methods: The pilot test included 6 families (27 participants) who took part in a family model of diabetes self-management education (DSME) using an intervention-driven pre- and posttest design with the aim of improving glycemic control as measured by A1C. Questionnaires and additional biometric data were also collected. Researchers systematically documented elements of feasibility using participant observations and research field reports. Results: More than three-fourths (78%) of participants were retained in the study. Posttest results indicated a 5% reduction in A1C across all participants and a 7% reduction among those with type 2 diabetes. Feasibility of an in-home model with extended family members was documented, along with observations and recommendations for further DSME adaptations related to blood glucose monitoring, physical activity, nutrition, and medication adherence. Conclusions: The information gained from this pilot helps to bridge the gap between knowledge of an evidence-based intervention and its actual implementation within a unique minority population with especially high rates of type 2 diabetes and significant health disparities. Building on the emerging literature of family models of DSME, this study shows that the family model delivered in the home had high acceptance and that the intervention was more accessible for this hard-to-reach population.